Analisis Efektivitas dan Kontribusi Pajak Hotel terhadap Pendapatan Asli Daerah (PAD) Kota Medan - Arisandy Aruan, Deasy; Putri Purba, Dianty (E-Jurnal Akuntansi, 2021)
The purpose of this research is to find out how the effectiveness and contribution of hotel taxes in increasing the source of regional revenue. Sources of data used in this study are secondary data, there’s the form of targets and realization of hotel tax revenue and realization of regional revenue (PAD) Medan City from 2014 to 2018. The data analysis technique used in this study is to use descriptive analysis. To determine the level of effectiveness is to compare the hotel tax realization value with the hotel tax target that has been set by the Regional Government of Medan City. And to find out how to analyze the contribution of hotel tax to Regional Revenue (PAD) is to compare the value of hotel tax realization with the realization of regional revenue (PAD) in Medan City. The research result states that in 2014-2018, the effectiveness and contribution of hotel tax tends to fluctuate every year. The value of hotel tax effectiveness is in the value of 93-114% and is in the very effective criteria, except in 2015 entering the effective criteria. Meanwhile, the contribution is worth 5-7%, so that it is in the very poor criteria in increasing the regional revenue (PAD) of Medan City. Keywords: Hotel Tax; Regional Revenue (PAD).